(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The experiment was conducted during autumn season in (2014) in horticulture station belonging to the Ministry of Agriculture at Mahaweel site (20km North of Hilla City) in a Sandy clay loam soil, using a systematic arrangement of whole-plots, to study the effects of irrigation water salinity and the addition of organic and mineral fertilizers in the leave nutrients contents (N, P, K), and cabbage growth & yield. The experiment included 72 treatments of overlap between the 2 factors, the first factor represented the salinity of irrigation water (at 3 levels; 1.4, 3, & 6). The second factor represented organic and mineral fertilizers (T) with 8 different fertilizer transactions are (control), (compositing corn cobs, 20 tons/H), (composting cattle wastes: 20 tons /H), (composting corn cobs + composting cattle wastes: 20 tons/H at a 1:1Ratio), (DAP 400kg/H), (composting corn cobs 20 tons/H +DAP 400Kg/H), (composting cattle wastes 20tons/H +DAP 400Kg/H),and (composting corn cobs + composting cattle wastes: 20 tons/H at a 1:1Ratio)+ (DAP 400kg/H), and 3 replicates. The results are summarized as follows: There was a significant decline in the leaves contents of Nutrient (N, P, and K),the ratio of Potassium to Sodium dry weight of leaves, chlorophyll content in leaves rising of irrigation water salinity, However all the previously mention characteristics were significant raised with addition of organic and chemical fertilizers whether alone or as mixture, the mixed treatments gave the higher averages in all of the pervious characteristics.